The Gender Attitude of the Lebanese October Revolution - Al Alieh, Ayah (2020)
The Lebanese political landscape has long been dominated by an underlying confessional balance of power. In 2019 and 2020, however, the October 17 Revolution emerged to challenge the status quo, exerting pressure on the Lebanese government to push for systemic reform, thereby bringing a decade-long political structure to the verge of collapse. Among the structural challenges brought against the confessional regime are women taking the lead in the reform and revolutionary movement. A role that exposed confessionals not only as a communitarian share of power, but also as a male order regime. More importantly, however, the protest has set in motion an irreversible momentum that shaped a new public attitude toward politics and society in rejection of women subjugation. This thesis explores the fundamentals of Lebanese gender perspective that is being reshaped by the public protest movement. It surveys diverse online and phone samples of respondents to highlight common gender-based themes and emerging perceptions as they relate to women and political representation. The findings demonstrate that a convergence is developing across political divide in support of gender quotas as well as in reforming civil status laws. The findings are indicative of an overwhelming bottom-up, cross confessional, and politically diverse drive, undermining patriarchal elites’ reluctance to women’s civil and political equality. They also stipulate that 2022 elections’ support will be highly formulated by candidates’ adoption to women political and civil rights.